Effect of Centrifugal Adhesion of Pollutant on Thermal Elastohydrodynamic of Water-lubricated Hybrid Journal Bearing - Zhang Tonggang; Wang Youqiang; Wang Limei; Xu Caihong (Jixie chuandong)
The elastohydrodynamic lubrication geometric model of centrifugal pollutants adhesion is established. The thermal elastohydrodynamic numerical simulation of water-lubricated hybrid journal bearings considering its lubricant pollution problem is carried out by using the Reynolds equation with thermal effect. The effect of centrifugal attachment on the surface texture of the bearing pad and the film thickness,pressure change of the lubricating film in the contact zone are studied. The influence of the film thickness and pressure of the contact zone are analyzed as the contaminants are centrifugally attached to plug the water inlet. The influence of the adhering layer on the temperature field of the contact zone is obtained. The results show that the centrifugal attachment of pollutants effectively improves the roughness of the surface of the bearing pad and alleviates the film thickness fluctuation in the contact area. The greater the degree of clogging of the pollutant to the water inlet,the smaller the water supply pressure,the smaller the minimum film thickness,the greater the maximum pressure,which is not conducive to bearing lubrication. The contaminant adhering layer has an effect on the temperature field of the contact zone of the water-lubricated hybrid journal bearing. When the difference of the physical parameters of the pollutant and the bearing material vary largely,the temperature field changes greatly.